The Analysis of SQDC Based on Lean Concepts in the Daily Workwear Production Process at PT. XYZ’s Convection Company - Rakhmanhuda, Iffad; Rusindiyanto; Pradanarka, Andyas Mukti (2477 - 6165, 2024)
The garment industry, a cornerstone of Indonesia's economy, faces persistent challenges in efficiency and quality, as evidenced by PT. XYZ's struggles with uneven stitching, loose buttons, and stained fabric in daily workwear production. To address these issues, this study employs Lean Manufacturing principles integrated with the SQCDMPE framework. By utilizing tools like fishbone diagrams and SQCDMPE analysis, root causes of production inefficiencies were pinpointed. Recommendations include implementing stringent quality controls, enhancing worker training, and optimizing operational processes to minimize waste and improve overall efficiency. These strategies aim to streamline production at PT. XYZ, enhancing product quality and meeting customer demands effectively in the competitive global garment market.